Prevalence and predictors of psychotropic medication use: results from the Northern Ireland Study of Health and Stress. (15th September 2014) - Benson, T.; O'Neill, S.; Murphy, S.; Ferry, F.; Bunting, B.
Abstract : Background: To identify the predictors of psychotropic medication use and to determine rates and patterns of use in Northern Ireland (NI) among the general population and various subgroups. Method: Analysis of data from the NI Study of Health and Stress, a representative household survey undertaken between 2004 and 2008 with 4340 individuals. Respondents were asked about prescribed psychotropic medication use in the previous 12 months along with a series of demographic questions and items regarding experience of traumatic life events. Mental health disorders were assessed using the World Health Organization's Composite International Diagnostic Interview. Results: Females, individuals aged 50–64 years old, those who were previously married, and those who had experienced a traumatic lifetime event were more likely to have taken any psychotropic medication. Use of any psychotropic medication in the population in the previous 12 months was 14.9%. Use among individuals who met the criteria for a 12-month mental health disorder was 38.5%. Almost one in ten individuals (9.4%) had taken an antidepressant. Conclusions: Compared with other countries, NI has high proportions of individuals using psychotropic medication in both the general population and those who met the criteria for a 12-month mental disorder. However, these results still suggest possible under treatment of mental disorders in the country. In addition, rates of use in those with no disorder are relatively high. The predictors of medication use are similar to findings in other countries. Possible research and policy implications are discussed.